Spread of hyperplastic pulmonary neuroendocrine cells into air spaces (S.H.I.P.M.E.N.T.S): A proof for artifact. (November 2019) - Pelosi, Giuseppe; Nesa, Francesco; Taietti, Davide; Servillo, Sascia Pietro; Papanikolaou, Nikolaos; Zompatori, Maurizio; Meroni, Alberto; Harari, Sergio; Incarbone, Matteo
Graphical abstract: Highlights: Spread through air spaces is suggested to be invasion way of lung parenchyma. Spread through air spaces has been described around lung neuroendocrine neoplasms. Spread through air spaces may be made up by hyperplastic neuroendocrine cells. Spread through air spaces is likely to be an ex vivo artifact due to tissue manipulation. Abstract: Objectives: Spread through air spaces (STAS) is a recently proposed invasion way of lung cancer, including neuroendocrine (NE) neoplasms. However, if this phenomenon is a real one or an artifact while manipulating lung specimens, it is still matter of debate. Material and methods: Three consecutive patients with newly diagnosed diffuse idiopathic pulmonary NE cell hyperplasia (DIPNECH) were reviewed for STAS. Results: In well-fixed lung specimens, DIPNECH was seen to coexist with atypical carcinoid, bifocal typical carcinoid and adenocarcinoma in the three patients, respectively. While STAS was not observed at the growing edges of tumors, a few freely-floating aggregates of hyperplastic NE cells within air spaces were noticed to emanate from foci of NE hyperplasia and tumorlets and in intimate association with normal bronchiolar cells and erythrocytes to denote artifactual derivation upon tissue manipulation. Conclusions: Traveling of hyperplastic NE cells through air spaces is likely to artifactually occur via knife, surgeon or other way, thus challenging invasion by STAS.